Determination of Reactive Black 5 (RB5) by differential pulse anodic stripping voltammetric technique / Nur Syamimi Zainudin and Nur Aqilah Abdul Rahman - Zainudin, Nur Syamimi; Abdul Rahman, Nur Aqilah (Universiti Teknologi MARA Negeri Sembilan, 2021)
Dyes are aromatic organic compound which have an affinity towards the substrate to which they are being applied to. The presence of dyes in wastewater samples is not safe for human even at low level. The presence of dyes in wastewater which are discharged from textile industry must be analysed. Hence, a precise, fast, accurate, simple and inexpensive analytical method with low detection limit is needed for the determination of dyes in wastewaters. The differential pulse anodic stripping voltammetric (DPASV) technique using bare glassy carbon electrode (GCE) as a working electrode and phosphate buffer at pH 4.2 as a supporting electrolyte has been proposed for Reactive Black 5 (RB5) determination. Several experimental voltammetric parameters were being optimized for obtaining a maximum response before analytical validation of the proposed technique being carried out. The optimum parameters were initial potential (Ei) = +0.3 V, end potential (Ef) = +1.0 V, scan rate (v) = 0.04 V/s, accumulation time (tacc) = 50 s, accumulation potential (Eacc) = 0.4 V and pulse amplitude = 0.075 V. The well-defined anodic peak appeared at 0.77972 V. The response was linear from 0.5 to 1.25 mg/L (R2=0.9986) with LOD of 0.050 mg/L. The relative standard deviation (RSD) achieved were 0.08 %, 0.62 % and 0.50 %, respectively for three consecutive days. The % recovery range achieved was from 89.71 % to 111.15 %. It can be concluded that the proposed technique is precise, accurate, inexpensive, fast and has a potential to be an alternative analytical technique for RB5 analysis. The proposed method will in the future be tested for the amount of RB5 in the wastewater samples from textile industry.